Exploring the Interconnection: Employee Diff, Board Gender Diversity, and Earnings Management - Hasan, Nadif Ahmad; Lestari, Dwi Indah (Journal of Accounting Science, 2024)
General Background: The COVID-19 pandemic caused significant economic disruptions, leading to reduced demand and sales across various sectors in Indonesia, including manufacturing. Specific Background: This study focuses on manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022 to investigate the impact of employee difference (diff) and board gender diversity on earnings management. Knowledge Gap: Previous research offers conflicting findings on the relationship between board gender diversity and earnings management, necessitating further exploration during the COVID-19 period when layoffs were prevalent. Aims: This study aims to empirically assess how employee diff and board gender diversity influence earnings management, contributing to better decision-making by investors and stakeholders. Results: The findings indicate that employee diff positively affects earnings management, while board gender diversity does not have a significant impact. Novelty: Conducted during the COVID-19 period, this research uniquely considers employee diff as a critical factor in earnings management, reflecting pandemic-related challenges. Implications: Investors and stakeholders should focus on employee diff when analyzing financial statements to avoid misinformed decisions, while also recognizing that board gender diversity may not significantly mitigate earnings management practices